The effectiveness of peer information toward a change in knowledge and attitude toward child marriage: A literature review - Wahyuningsih, Sri; Musviro, Musviro; Hayati, Nurul (Universitas Airlangga, 2025)
Introduction: Child marriage is a serious global problem because it can have negative consequences for children, families, and communities. Peer information has been considered as one strategy to reduce child marriage. Objective: This study evaluated the effectiveness of peer information in changing knowledge and attitudes towards child marriage. Methods: The study is carried out by systematically searching academic databases and a bibliography of relevant articles. There are 5 articles discussed from several countries and peer information is presented through group meetings or discussion forums. Results: Studies in several countries show that information passed on through peers can increase understanding and positive attitudes towards child marriage. Through education, interaction with peers is effective in informing adolescents about the risks of child marriage and encouraging healthy attitudes and behaviors related to reproductive health. Conclusion: Providing education through peers can be done for adolescents related to the risk of child marriage, so they will be able to determine the steps that must be taken so that the rate of child marriage decreases. Keywords: attitude; change in knowledge; child marriage; peer information